Diseño de equipo para la separación primaria de los sólidos de las aguas residuales en las empresas porcinas en Cuba (2019)
In the Work the literature is deepened about the aspects that characterize the generation of residuals in the Pig Farms in general and in particular those that exist in Cuba. Some aspects related to the equipment used in the primary separation of the solids from the waste water of the Swine Companies were reviewed, to select the most appropriate from the point of view of the necessary capacity, economy, simplicity of operation and maintenance, and effectiveness. Ultimately, a Conveyor / Strainer by Endless Screw is selected as the base equipment for the separation, the necessary capacity, its basic dimensions and fundamental operating parameters are calculated and the reduction motor is selected for its operation. Finally, the conveyor shaft is designed and calculated using the elastic foundation beam analysis scheme and the bearings are designed and calculated using a FEROFOM plastic material.